"¿Politizando la maternidad o maternalizando la política? Ciudadanía y participación política de las mujeres de los barrios del sur de san José, 1950-1980" - Ramírez Achoy, Jéssica (2011)
This article studies citizenship, political participation and urban facilities in south San losé, specifically the Luna Park neighborhood. The topic was studied in relation to the forms of control and resistance and the rule of motherhood for women to participate in the communal public space. Emphasis ¡s placed on the work of the Club de Madres, created in 1974 and the role of the Junta Progresista.